2013
DOI: 10.1371/journal.pone.0063687
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation Is Required for Secretion and Mitosis in C. elegans

Abstract: N-glycosylation of proteins is an essential process, and N-glucans serve as important beacons in protein folding and ER associated degradation. More importantly, N-glycosylation increases the structural repertoire of proteins because the addition of the N-glucan on proteins will serve as a base for further sugar additions in the Golgi apparatus, and hence complex three-dimensional structures can be build. N-glycosylation is mediated by the ER-resident OST complex, which is essential throughout eukaryotes. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
(35 reference statements)
2
23
0
Order By: Relevance
“…Over 80% of plasma membrane proteins are N-glycosylated in the ER, and this modification is essential for protein folding, function and stability. We have previously shown that depletion of OST complex components leads to secretion defects (Stevens and Spang, 2013). Here, we report that N-glycosylation is important for cell adhesion and cell polarity, suggesting a role for N-glycosylated proteins in the compartmentalization of the plasma membrane.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Over 80% of plasma membrane proteins are N-glycosylated in the ER, and this modification is essential for protein folding, function and stability. We have previously shown that depletion of OST complex components leads to secretion defects (Stevens and Spang, 2013). Here, we report that N-glycosylation is important for cell adhesion and cell polarity, suggesting a role for N-glycosylated proteins in the compartmentalization of the plasma membrane.…”
Section: Introductionmentioning
confidence: 63%
“…We have reported previously that reduced N-glycosylation leads to severe cytokinesis defects and delayed development (Stevens and Spang, 2013). The embryos that were able to successfully complete cytokinesis under those conditions, lost the adhesion between AB and P1 cells ( Fig.…”
Section: Ribo-1(rnai) Embryos Have Spindle Orientation Defectsmentioning
confidence: 78%
See 3 more Smart Citations